Perancangan Konten Kampanye "Blibli for Business Insight Day" sebagai Iklan Digital di PT Global Digital Niaga - Akbar Gilang Permana; Guruh Ramdani (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The design of the Blibli for Business Insight Day campaign focuses on analyzing the implementation of digital marketing strategies through a creative and strategic design approach. This study employs the STP (Segmentation, Targeting, and Positioning) framework, Design Thinking, and the Multimedia Development Life Cycle (MDLC) method to create effective B2B marketing materials. The campaign was developed through active participation, observation, interviews, and a comprehensive literature review. It aims to produce content that resonates with the target B2B audience by integrating design thinking with marketing strategies. The research highlights how the combination of design and marketing strategies helps strengthen the audience’s understanding of the value of the solution and the reliability of the product. Furthermore, the campaign supports business decision-making processes by delivering educational visual media. The primary goal of the campaign is not only to promote Apple products but also to educate companies on the operational efficiency of utilizing Apple products in their business processes, showcasing their benefits for long-term business success.